Secondary outcomes from the pediatric obsessive compulsive disorder treatment study II - Conelea, Christine A. (J Psychiatr Res, 2017)
The Pediatric Obsessive-Compulsive Disorder Treatment Study II (POTS II) investigated the benefit of serotonin reuptake inhibitor (SRI) augmentation with cognitive behavioral therapy (CBT). Primary outcomes focused on OCD symptom change and indicated benefit associated with a full course of CBT. Given that the majority of youth with OCD suffer from significant comorbid symptoms and impaired quality of life, the current study examined POTS II data for effects on secondary outcomes. Participants were 124 youth ages 7–17 years with a primary diagnosis of OCD who were partial responders to an adequate SRI trial. Participants were randomized to medication management, medication management plus instructions in cognitive behavioral therapy (CBT), or medication management plus full CBT. Acute effects on non-OCD anxiety, depression, inattention, hyperactivity, and quality of life were examined across treatment conditions. Improvement across treatment was observed for non-OCD anxiety, inattention, hyperactivity, and quality of life. Changes were generally significantly greater in the group receiving full CBT. Child-rated depression was not found to change. OCD-focused treatment lead to improvement in other areas of psychopathology and functioning. For youth who are partial responders to SRI mono-therapy, augmentation with full CBT may yield the greatest benefit on these secondary outcomes. CLINICAL TRIALS REGISTRATION: Treatment of Pediatric OCD for SRI Partial Responders, Clinicaltrials.gov Identifier: NCT00074815, http://clinicaltrials.gov/show/NCT00074815.